The Effect of Linear Alkylbenzene Sulfonate on Corrosivity of Vehicle Shampoo from Overproduction Softener Production in Industry - Raisa Syifa Alzena Yulianto; Cintiya Septa Hasannah; Meka Saima Perdani; Farradina Choira Suci (Universitas Tribhuwana Tunggadewi Malang, 2024)
Indonesia is one of the countries with a significant number of laundry services, which has led to the emergence of numerous companies engaged in the production of high-quality softener products. This extensive softener production has resulted in a considerable surplus of the product, which can potentially harm the environment. This study aimed to process the excess products produced by the softener industry into vehicle shampoo and LAS (Linear Alkylbenzene Sulfonate), the main component of vehicle shampoo. We will achieve this through trial-and-error mixing methods and optimal variations. We aim to create products with sales value that the public can use to wash vehicles at a more economical price while maintaining quality comparable to commercial products. The optimal variation results obtained from this research were 40 ml of fragrance, 50 ml of Sodium Laureth Sulfate (SLES) Texapon, and 40 g of LAS, with test results of pH 7.92 and density 1.025 g.cm-3. The viscosity was found to be 2.41 Pa.s, the foaming power was 91.67%, and the corrosivity was 0.09291 mm/year. These results showed that the vehicle shampoo meets corrosion resistance standards.Â